Steady and transient performance of a model pump-turbine at off-design conditions: turbine mode. Issue 7 (March 2019) - Hu, J H; Yang, J D; Zeng, W
Abstract: Model Experiments including steady-state and hydraulic transient experiments are essential to study the hydraulic characteristics of pump turbines in turbine mode. They can be used as verification of CFD calculations. Moreover, some special and complicated transient processes can only be examined through experimental research. This paper reports a series of steady-state and hydraulic transient experiments performed on an open-loop pumped storage test rig. First of all, steady-state experimental results were presented, including the measured characteristic curves by adjusting the sphere valve, characteristics of pressure pulsations, and the hill-chart. Subsequently, three kinds of transient experiments were conducted under a fixed guide-vane opening (GVO) to dynamically investigate characteristic curves. The first kind of dynamic tests was conducted with continuous operation of the sphere valve while the unit rotated at the rated value by connecting to the power grid. This was followed by the load rejection experiments. In the third type of transient experiments, the recirculation pump delivering water to the upstream and downstream tanks was shut down when the unit was in designed operation and synchronized to the power grid. As the water level in the upstream tank continued to decrease, the unit experienced a special dynamic process. In this process, the flow discharge and the water head were oscillating periodically while the pump-turbine was switching back and forth from the turbine mode to the reverse rotation pump mode with a constant rotational speed. This transient test was completely different from the others and was regarded as an individual method to investigate the characteristic curves dynamically. Finally, characteristics curves under a constant GVO obtained by these tests were compared and analyzed.